Knowledge, attitude, and practice of performing prayers (Salat) among Muslim patients in hospital Langkawi, Kedah: Roles of muslim healthcare providers - Aris M.S.M.; Rani M.D.M.; Jaafar M.H.; Norazmi A.U.A.; Umar N.S. (American Scientific Publishers, 2024)
Indexed by Scopus/ERA